2010
DOI: 10.1007/s10488-010-0307-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Neighborhood Experiences and Psychiatric Distress for Individuals with Serious Mental Illness

Abstract: The present study examined the relationships between how research participants experienced their neighborhood, their neighborhood social climate, and psychological well-being. Participants (n = 525) were residents of supported housing programs who used mental health services at one of 17 community mental health centers in South Carolina. Hierarchical regression and mediation analyses were employed to answer research questions. Results suggest that neighbor relations, perceptions of neighborhood safety, and nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 55 publications
4
20
0
5
Order By: Relevance
“…For example, Kloos and Townley (2011) found that individuals who reported feeling safe in neighborhoods and perceiving a positive social climate (i.e., one that does not discriminate others based on race and is accepting of individuals with a mental illness diagnosis) reported less distress from psychiatric symptomatology. Numerous studies have demonstrated the important role that feeling safe and accepted has in the mental health recovery experiences of individuals with psychiatric disabilities.…”
Section: The Social Ecology Of Supported Housing Environmentsmentioning
confidence: 99%
“…For example, Kloos and Townley (2011) found that individuals who reported feeling safe in neighborhoods and perceiving a positive social climate (i.e., one that does not discriminate others based on race and is accepting of individuals with a mental illness diagnosis) reported less distress from psychiatric symptomatology. Numerous studies have demonstrated the important role that feeling safe and accepted has in the mental health recovery experiences of individuals with psychiatric disabilities.…”
Section: The Social Ecology Of Supported Housing Environmentsmentioning
confidence: 99%
“…In particular, sense of community may play an important role in improving mental health for people with serious mental illnesses. For example, the more that individuals with serious mental illnesses feel that they belong in their neighborhoods and are accepted by neighbors, the less psychiatric distress they report (Kloos & Townley, ). Further, in a study conducted by Gulcur, Tsemberis, Stefanic, and Greenwood (2007), participants who experienced more psychological symptoms reported lower levels of sense of community.…”
Section: Introductionmentioning
confidence: 99%
“…La vivienda ha dejado de ser exclusivamente un tema de bienestar social, sino más bien se considera un componente importante del tratamiento y de las políticas en salud mental 17 . La vivienda es una fuerza estabilizadora en la vida cotidiana que forma la base sobre la que una persona puede establecer una rutina diaria, por ello en Chile debe existir un cambio de modelo, desde uno centrado en los recursos disponibles a otro centrado en las necesidades de los usuarios.…”
Section: Discussionunclassified
“…Los programas residenciales son dispositivos generados para que vivan las personas con TMS. Estos proporcionan un marco normalizado donde se abordan las diferentes problemáticas del individuo, posibilitando una actuación integral y global, no centrada en la institución sino en las necesidades del usuario [15][16][17] . En estos lugares se fomenta la autonomía de las personas a través del desarrollo de sus habilidades sociales.…”
unclassified